Optimizing The Use Of Government Credit Card And Cash Management System Virtual Account as a Tool For Paying For State Expenditures in Pusbangkom Management System BPSDM Ministry of PUPR - Rusmayanthy, Rusmayanthy; Karunia, R. Luki; Sutrisno, Edy (UNIVERSITAS PAKUAN, 2023)
This research has limitations on the discussion of optimizing the use of KKP and CMS VA as a means of payment for state spending in the Pusbangkom Management BPSDM Ministry of PUPR. This research is In this study, researchers used qualitative methods aimed at studying what phenomena were felt by research subjects, such as behavior, motivation, actions, perceptions, and others descriptively in the form of language and words so as to enable researchers to examine the subject matter in more detail. in depth, especially if there is still uncertainty about the research problem. In addition, qualitative research is also used to explain theories, to provide certainty regarding whether or not the data in this study are correct. The implementation of the use of non-cash state payment instruments, namely Government Credit Cards (KKP) and Cash Management System Virtual Accounts (CMS VA) at the Pusbangkom Management Satker of the BPSDM Ministry of PUPR has been running since 2019 until now (Year 2022), but it is known from research results that actual use is still very low, reaching only 2% of the DIPA ceiling due to the high use of cash. The not optimal use of KKP and CMS VA is influenced by internal and external factors, including internal factors, lack of leadership commitment related to the use of KKP and CMS VA , lack of HR competence , no SOP for procedures for using KKP and CMS VA. External Factors There is an additional Surcharge fee from the merchant / store provider for KKP and CMS VA transactions , There are bank account requirements for CMS VA payments , There is no punishment system from regulators (BUN). Strategic steps as an effort to optimize the use of KKP and CMS VA, namely Re-Collection of KKP and CMS VA , Setting targets for the use of KKP and CMS VA , Preparation of SOPs and Memorandum of Service for KKP and CMS VA , Strengthening HR , Conducting periodic Monitoring and Evaluation.